Kepatuhan Wajib Pajak Melalui Pengetahuan Perpajakan dan Kepercayaan pada Pemerintah - Zulkarnain Zulkarnain; Elvan Alvian Iskandar (Cakrawala Repositori IMWI, 2019)
This research is aimed at finding influence of: (1) Taxation knowledge on individual taxpayer’s compliance, (2) Trust in government on individual taxpayer’s compliance, and (3) Both taxation knowledge and trust in government on individual taxpayer’s compliance. The population on this research are 62 employee of PT Usaha Giat Sejahtera. Collecting data using primary data source on the form of questionnaire. This research used some perquisite tests analysis such as normality test, multicolinearity test, and heteroscedasticity test. This research use double linear regression analysis as for the data analysis technique. The research reveal that the taxation knowledge gives positive influence on taxpayer’s compliance. Trust in government did not influence taxpayer’s compliance. Taxation knowledge and trust in government simultaneity show a positive influence.